2022
DOI: 10.1038/s41598-022-08865-y
|View full text |Cite
|
Sign up to set email alerts
|

Subretinal fluid disturbs the retinal venous blood flow in central serous chorioretinopathy

Abstract: The significance of subretinal fluid in the retinal blood flow is unclear. Here, we evaluated the association between subretinal fluid (SRF) and retinal blood flow in eyes with central serous chorioretinopathy (CSC) using a retinal functional imager (RFI) and optical coherence tomography angiography (OCTA). In this retrospective case–control study involving 26 eyes from 18 CSC patients and 25 eyes from 21 age- and sex-matched controls, we found that the CSC group showed significant differences from the control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Other studies have suggested that the accumulation of SRF usually indicates dysfunction of the RPE, including disruption of the outer blood-retinal barrier and defects in the drainage system and pump function of the RPE [25] . This dysfunction is related to the release of pro-inflammatory factors, enhanced permeability mediated by VEGF, protein hydrolysis induced by matrix metalloproteinases, and regulation of cytoskeletal proteins [26] . In our study, DME eyes with two OCT biomarkers, SRF and HRF, achieved better results with combination therapy.…”
Section: Resultsmentioning
confidence: 99%
“…Other studies have suggested that the accumulation of SRF usually indicates dysfunction of the RPE, including disruption of the outer blood-retinal barrier and defects in the drainage system and pump function of the RPE [25] . This dysfunction is related to the release of pro-inflammatory factors, enhanced permeability mediated by VEGF, protein hydrolysis induced by matrix metalloproteinases, and regulation of cytoskeletal proteins [26] . In our study, DME eyes with two OCT biomarkers, SRF and HRF, achieved better results with combination therapy.…”
Section: Resultsmentioning
confidence: 99%
“…CSC is a part of the pachychoroid spectrum disorders, and is characterized by serous retinal detachment, RPE alterations and dilation of the choroidal vessels. Retinal blood flow velocity and blood flow rate were reported to be lower in eyes with CSC as compared to healthy eyes [ 18 ]. Therefore, it has been speculated that MR pathway overactivation may reduce retinal blood flow.…”
Section: Discussionmentioning
confidence: 99%